ANALISIS EFISIENSI DAN EFEKTIVITAS ANGGRAN PENDAPATAN DAN BELANJA DAERAH - Insaniah, Nurul Qalbi; Arizah, Ainun (AKRUAL : Jurnal Akuntansi dan Keuangan, 2025)
This study analyzes the efficiency and effectiveness of the APBD of Maros Regency for the years 2021-2024. Regional autonomy is essential for improving welfare, encouraging innovation, and enabling the community to oversee the management of the APBD. Budget efficiency refers to the optimal use of resources, while effectiveness relates to the achievement of regional development goals. The methodology used is quantitative descriptive with efficiency and effectiveness ratios, utilizing secondary data from the Budget Realization Report of the Maros Regency Financial Management Agency (BPAKD). The results indicate that the efficiency of the Maros Regency APBD is not optimal, with efficiency values for each year as follows: 2021 (100.7% - inefficient), 2022 (94.7% - less efficient), 2023 (100.7% - inefficient), and 2024 (103.8% - inefficient). This suggests that budget preparation does not always accurately analyze needs. On the other hand, the effectiveness of the Maros Regency APBD is considered good, with effectiveness values as follows: 2021 (101.7% - very effective), 2022 (98.7% - effective), 2023 (101.7% - very effective), and 2024 (98.6% - still effective). This indicates good budget management.